IDENTIFICATION AND ANALYSIS OF TAX RISKS THROUGH TAXPAYER SEGMENTATION - Elbaeva M. R. (American Journals, 2025)
This article analyzes theoretical and practical approaches to identifying and managing tax risks through segmentation of taxpayers' activities. It is argued that the financial activities of any business entity are closely related to various risk factors and that it is necessary to form an effective risk management system to reduce the negative consequences of these risks.The study examines in detail the nature of tax risks, the factors that cause them, and the mechanisms for managing them. It is noted that the current tax risk management system is not sufficiently developed, which creates the need for institutional development and training of qualified specialists in this area. It also the risk effective management instrument as tax payers’ activity segmentation main stages illuminating is given.
Keywords: Tax risks; tax risk assessment; tax relations; tax policy; taxpayer segmentation.